Using Digital Data Gathering to improve data collection. Issue 1 (2nd January 2016) - Matturi, Kai
ABSTRACT: One of the ways in which aid actors have responded to the growing need for good quality data to inform decision-making processes has been to invest in information communication technology to improve data collection and analysis. The specific information communication technology approach that has been used by Concern Worldwide is Digital Data Gathering. This refers to gathering data using an electronic handheld device such as a smartphone or data pen. As with any approach it has its advantages and limitations. This article shares the lessons and challenges that Concern has had in the utilisation of Digital Data Gathering.